2020
DOI: 10.1021/acsami.0c17538
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing of Liquid Crystal Elastomer Foams for Enhanced Energy Dissipation Under Mechanical Insult

Abstract: Polymer foams are an essential class of lightweight materials used to protect assets against mechanical insults, such as shock and vibration. Two features are important to enhance their energy absorption characteristics: the foam structure and the matrix phase mechanical behavior. This study investigates novel approaches to control both of these features to enhance the energy absorption capability of flexible lattice foams. First, we consider 3D printing via digital light processing (DLP) as a method to contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 53 publications
0
62
0
Order By: Relevance
“…One of the most exciting but often overlooked applications for liquid crystal elastomers (LCEs) is for use in strain-rate-dependent impact absorbing devices. [1][2][3][4][5] In 2001, Clarke et al reported that LCEs -which incorporate the anisotropic ordering of liquid crystals into elastic polymer networks -demonstrate elevated loss tangents (𝑡𝑎𝑛(δ) = G''/G) as high as 1.5 when held at temperatures between their glass transition and nematic-to-isotropic transition temperatures (Tg and TNI respectively). 6 These values of 𝑡𝑎𝑛(δ) correspond to highly viscous and dissipative materials and are far greater than values (~0.1) found in traditional isotropic elastomers.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most exciting but often overlooked applications for liquid crystal elastomers (LCEs) is for use in strain-rate-dependent impact absorbing devices. [1][2][3][4][5] In 2001, Clarke et al reported that LCEs -which incorporate the anisotropic ordering of liquid crystals into elastic polymer networks -demonstrate elevated loss tangents (𝑡𝑎𝑛(δ) = G''/G) as high as 1.5 when held at temperatures between their glass transition and nematic-to-isotropic transition temperatures (Tg and TNI respectively). 6 These values of 𝑡𝑎𝑛(δ) correspond to highly viscous and dissipative materials and are far greater than values (~0.1) found in traditional isotropic elastomers.…”
Section: Introductionmentioning
confidence: 99%
“…However, to the best of our knowledge, 2W‐SMPAs have not been reported to date. [ 13 , 14 ] So, the design, preparation and characterization of 2W‐SMPAs with reversible shape‐morphing capability and porous structures are all new challenges. Herein, we present the first 2W‐SMPA sample, for which reversible shape deformation from a permanent shape (permanent shape 1) to the other permanent shape (permanent shape 2) under stimuli has been realized (Figure 1b ).…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Moreover, nematic LCEs [1,7] exhibit unique mechanical properties, such as a higher viscoelasticity and a soft elasticity, by which the materials can deform under little increase in stress. The ability to reversibly switch them to a classic rubber elasticity, which is attained in an isotropic state by increasing the temperature (T), or light irradiation, [8][9][10][11] can further provide an LCE with a dynamic nature in terms of mechanical damping, [12][13][14] adhesion, [15,16] and friction. [17] Although their applicability as dynamic functional units has been well demonstrated in these systems, the changes to the underpinning mechanical properties, for example, stress-strain and viscoelastic responses associated with the phase transition, remain largely unexplored.…”
mentioning
confidence: 99%